Effectiveness of Raskin Program Implementation in Piawas Village, Belimbing Hulu District, Melawi District - Wiro Wiro; Jajat Sudrajat; Abdul Hamid A. Yusra (Jurnal Sains Pertanian Equator, 2019)
The purpose of this study is to determine the effectiveness of the implementation of the Raskin program that has been carried out in Piawas Village. The study was conducted by survey and data were analyzed using descriptive, quantitative and qualitative approaches. 33 people were interviewed, consisting of 24 men and 9 women.The distribution of rice for the poor can be said to have run effectively, which is seen from the six indicators of research (right on target, the right amount, the right price, on time, the right administration, and the right quality) shows an average figure of 97.47%. Indicators on target reach 84.85% proportion, exact sales price of Rp.4,000, - per kilogram of 100%, exact amount in the weight of 15 kg per head of family is 90.90%, on time in each distribution of 100%, appropriate administration of distribution of 100 %, and the right quality of Raskin rice is worth 100%. Keywords: Effectiveness of Raskin, Price Subsidies